2019
DOI: 10.1002/er.4933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cell compression on the performance of a non–hot‐pressed MEA for PEMFC

Abstract: In this study, effect of cell compression on the performance of a non-hot press membrane electrode assembly (MEA) for a polymer electrolyte membrane fuel cell (PEMFC) is presented. The MEA is made without hot pressing, by carefully placing the gas diffusion electrodes (GDEs) and a membrane in a fuel cell fixture. Cell performance is assessed at five different compression ratios between 3.6% and 47.8%. It has been shown that ohmic resistance of the cell, mass transport resistance of reactants, charge transfer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…The RH of the inlet gases also played a role in the GDL flooding and it was suggested to decrease the compression ratio with higher gas humidity. [ 526 ]…”
Section: Catalyst Layer Preparation Methodsmentioning
confidence: 99%
“…The RH of the inlet gases also played a role in the GDL flooding and it was suggested to decrease the compression ratio with higher gas humidity. [ 526 ]…”
Section: Catalyst Layer Preparation Methodsmentioning
confidence: 99%
“…Using high stoichiometry and an ensuring even distribution of the double layer capacitance, the simple planar electrode models can be used to analyse data from the impedance spectra [16]. The simple equivalent circuit approach has, therefore, been used in a high number of studies and practical models for system monitoring in fuel-cell technology [7,8,11,12,[22][23][24]. In the system monitoring application, EIS is very attractive as it (i) requires only minimal additions in the required hardware and (ii) enables for a significantly faster means of obtaining data in contrast to recording of a complete polarization curve [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this technique is aggressive and can damage the membrane, the catalyst layer as well as decrease the porosity of the GDL. [170][171][172] It was recently reported that the degradation of the membrane can induce cracks in the catalyst layer, degrading the TPB and overall reduce the efficiency of the MEA. [173] An interesting path to overcome this issue was suggested by grafting organic free radical scavengers in the polymer matrix [174] or non-organic ones.…”
Section: Catalyst Layer and Ionomer Interfacementioning
confidence: 99%